Microvascular lesions and changes in cell proliferation and death, and cytokine expression in the placentas of mice experimentally infected with Equid Herpesvirus 1 - Zanuzzi, Carolina Natalia (2016)
This study describes the changes observed in the placentas of mice experimentally infected with an abortigenic strain of EHV-1 at mid-pregnancy and euthanized at days 3 and 4 post-infection. We analyzed microscopic vascular alterations, cell proliferation and death by immunohistochemistry, and the expression of IFN-γ, TNF-α and the IL-10 by qPCR and flow cytometry. Infected mice showed slight respiratory signs and ruffled fur during the first two days post-infection. Virus isolation and DNA detection were positive only in the lungs of the infected mice. Vascular congestion, increase in the labyrinth area, and a significant reduction in fetal capillary endothelium surface of infected placentas were found. Cell proliferation was significantly reduced in the infected placentas, whereas the apoptosis was significantly increased. IL10, TNF and IFN-γ showed different expression in the infected placentas and uteri. The effects of EHV-1 during pregnancy depend on different pathogenic mechanisms in which vascular alterations, and cell death and proliferation and local cytokine changes are compromised.